The Impact of Social Networking Sites on Arab Literary Genres - Sherine Khatib, Sahar Mohamed Fathy, Ghada Kamal Sweilem (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Social media is one of the most important factors affecting various aspects of our life, and the problem is a large part of our awareness, tastes and visions in various fields. Literature has had a lot of change because of these sites. This research paper seeks to monitor, analyze, and understand its impact on reshaping the system of Arab literary genres.